Possibilities of Asia-Europe Cooperation on Energy Security - Krystosiak, Paulina B. (Możliwości współpracy azjatycko-europejskiej w kwestii bezpieczeństwa energetycznego, 2010)
Energy and its security play a dominant role in shaping the security strategies of many nations. There are broad similarities in the energy situation in Asia and Europe, such as a high import dependency and dependence on the Middle East. Energy security is therefore an issue of common concern in the two regions. Energy security also has a strategic dimension given the strong interdependence between the two regions. Any policy option chosen by one region will also have an impact on the other region. These spill-over effects have to be taken into account in the policy decisions.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 126, s. 211-219
Keywords: energy security; multirateral cooperation; international energy markets